Siesta characteristics mediated the association between siesta duration and sleep quality in Chinese incoming college freshmen - Huiying Wang; Jiali Li; Yaohui Han; Shilei Zhai; Yumeng Liu; Peipu Shen; Guifang Shen; Lishun Xiao (Scientific Reports)
Abstract To investigate the sleep quality of incoming college freshmen who have completed college entrance exams but have not yet entered college, to identify associated factors, and the mediating role of siesta characteristics on the relationship between siesta duration and sleep quality. This study included 6,519 incoming freshmen from two colleges in Xuzhou city, China. Weighted multiple linear regression (MLR) and binary logistic regression (BLR) were employed to investigate the factors associated with sleep quality. Mediation analysis was conducted to examine the influence of siesta characteristics on sleep quality and siesta duration. Stratified analysis was conducted based on gender and college level to examine the correlation between sleep quality and siesta durations (1–29 min, 30–50 min, ≥ 60 min). Both regression models found that longer siesta duration was a risk factor for poor sleep quality. Mediation analysis demonstrated that sleep position, the interval between lunch and the siesta, and the subjective rating of sleepiness 30 min after the siesta mediated this relationship. Male students with 30–59 min siestas, junior college freshmen with 1–29 min siestas, and undergraduate freshmen with ≥ 60 min siestas exhibited an increased risk of poor sleep quality compared to their counterparts without siestas. Furthermore, lifestyle behaviors and physical activity were also found to impact sleep quality. Longer siesta duration has been identified as a risk factor for sleep quality, especially in incoming undergraduate and male students. Some siesta characteristics mediate the relationship between them.